Re-evaluating standards of human subjects protection for sensitive health data in social media networks - Chu, Kar-Hai; Colditz, Jason; Sidani, Jaime; Zimmer, Michael; Primack, Brian (Social networks, 2021)
•There are no standards for network studies using social media data.•Consider ethics of consent, expectation of privacy, and personal health information.•Example study: can identify individuals affected by cancer via social media networks.•Guidelines needed to balance public health imperatives, research ethics, and privacy. This study addresses ethical questions about conducting health science research using network data from social media platforms. We provide examples of ethically problematic areas related to participant consent, expectation of privacy, and social media networks. Further, to illustrate how researchers can maintain ethical integrity while leveraging social media networks, we describe a study that demonstrates the ability to use social media to identify individuals affected by cancer. We discuss best practices and ethical guidelines for studying social media network data, including data collection, analysis, and reporting.